ON THE CHEMISTRY OF THE KEGGIN AL13 POLYMER: KINETICS OF PROTON-PROMOTED DECOMPOSITION - III. A GENERALIZATION ON THE DISSOLUTION RATES OF MINERALS - Furrer G.; Gfeller M.; Wehrli B. (My University, 1999)
The decomposition of the polynuclear Keggin Al13 species (Al13O4(OH)24(H2O)127+ or Al13) has been examined as a function of pH (2.06 =< pH =< 3.50), ionic strength (I = 0.1 and 1.0) and temperature (10°C =< T =< 65°C) using batch and flow-through reactors. The overall decomposition rates were found to be positively correlated with the activity of H+, ionic strength and temperature with half-lives ranging from 350 to 43,000 s. The decomposition rate was interpreted as a function of two parallel reactions, one first-order and one second-order with respect to [H+] -d[A113]dt=R1+R2 (1) where R1 = k1 [H+] [Al13] and R2 = k2 [H+]2 [Al13].For 25°C and I = 0.1, the rate constants k1 and k2 were determined as 0.0333 +/- 0.0016 M-1 s-1 and 2.59 +/- 0.62 M-2 s-1, respectively. The activation energies and the Arrhenius factors for an ionic strength of 1.0 were found to be Ea1 = 13.3 +/- 1.9 kJ mol-1, Ea2 = 44.9 +/- 4.9 kJ mol-1, A1(I=1.0) = 25.2 +/- 19.2 M-1 s-1, A2(I=1.0) = 1.62 109 +/- 3.12 109 M-2 s-1. While Ea1 and Ea2 do not depend on the ionic strength, the Arrhenius factors for I = 0.1 were obtained as A1(I=0.1) = 7.23 +/- 0.19 M-1 s-1 and A2(I=0.1) = 1.86 108 +/- 1.9 107 M-2 s-1. The apparent charge of the Al13 complex in the encounter reaction with a hydronium ion was calculated from the Arrhenius factors at various ionic strengths as 0.78. We postulate Al13 with a protonated bridging OH group as the precursor for the decomposition reaction, first-order in [H+]. The low value of the activation energy for the one-proton pathway is explained by an exothermic formation of the precursor HAl138+. The larger value of Ea2 indicates that the formation of a precursor with two adjacent protonated sites involves a positive reaction enthalpy. The half-life of several hundred hours at pH 5 indicates that Al13 may exist in natural waters, however, it may also be subject to continuous decomposition and reformation.